Myeloid Disease with the CSF3R T618I Mutation after CLL - Maria Eduarda Couto; Susana Bizarro; Domingos Sousa; Nelson Domingues; Isabel Oliveira; Gabriela Martins; Manuel R. Teixeira; Mário Mariz (Case Reports in Hematology)
Chronic lymphocytic leukemia (CLL) is frequently an indolent diagnosis, with most of the patients being under surveillance for long time. There is an increased risk of a second neoplasia in CLL, rarely hematological (in the myeloid lineage is even rarer). A 58-year-old male was diagnosed with CLL in 2012, remaining in regular surveillance until 2014. Then, the CLL progressed, and 6 cycles of rituximab, fludarabine, and cyclophosphamide were prescribed with partial response. He remained in surveillance and suffered 2 episodes of autoimmune hemolytic anemia until 2019. Then, the hemolytic anemia relapsed and a neutrophilia became evident (progressing slowly), as well as a thrombocytopenia and splenomegaly without adenopathy were found. The bone marrow aspirate showed a chronic myeloproliferative disease without dysplasia. A peripheral blood search for the CSF3R mutation (T618I) was positive, also suggesting Chronic Neutrophilic Leukemia (CNL). For a discrete monocytosis, a chronic myelomonocytic leukemia (CMML) was also considered. Hydroxyurea was then prescribed. The T618I CSF3R mutation is highly suggestive of CNL (being diagnostic criteria for CNL); however, this case may also suggest CMML as a possible diagnosis (there are other mutations in the CSF3R gene described for CMML, but not the T618I, which is highly exclusive of CNL according to the literature). To our knowledge, this is the first report of a possible CNL in a CLL patient (the opposite was already described in 1998).